A new miocene lacustrine mollusc fauna of the Dinaride Lake System and its palaeobiogeographic, palaeoecologic and taxonomic implications. (16th January 2013) - NEUBAUER, THOMAS A.; MANDIC, OLEG; HARZHAUSER, MATHIAS; HRVATOVIĆ, HAZIM
Abstract : Abstract:  The Dinaride Lake System, as one of the largest freshwater systems in the Neogene of Europe, is widely known for its exceptional mollusc fauna. During the Early and Middle Miocene, it displayed a major evolutionary hotspot resulting in a high level of endemicity. Despite advanced investigations in that region, comprehensive knowledge on the mollusc fauna of the Kupres basin is largely lacking. The herein presented results give insight into this outstandingly preserved fauna and are the base for a systematic revision of several supraspecific taxa among the Hydrobiidae. Because their phylogeny is poorly known, this study may serve as starting point for an overall systematic revision of this highly diverse family. Moreover, the faunal composition allows inferences on palaeobiogeography and hydrological connections within the Dinaride Lake System during the early Middle Miocene. About one‐third of the described taxa are restricted to the Kupres basin. The other taxa document faunistic relations to the coeval faunas of the Sinj, Drniš and Džepi basins. Phases of hydrological isolation, indicated by carbonate dominated lithology, coincide with a high frequency of sculptured morphologies within the gastropods. Phases of increased aridity led to high evaporation, a lowered lake level and enhanced carbonate production which seem to have promoted strongly calcified shells. The stratigraphic ranges of the species imply a depositional age of 15.5 ± 0.2 Ma (earliest Middle Miocene; Langhian). Among the Hydrobiidae Cyclothyrella gen. nov. and Pseudodianella gen. nov. are introduced as new genera. Bania obliquaecostata sp. nov., Melanopsis corici sp. nov., Nematurella vrabaci sp. nov., Prososthenia diaphoros sp. nov. and Prososthenia undocostata sp. nov. are described as new species. For the secondary homonym Melanopsis bittneri (Neumayr, 1880), the new name Melanopsis medinae nom. nov. is proposed.